Prevalence of Anemia Among Schedule Caste Women in Rural Area of Eastern Nepal - Sinha, Amar Kumar; Gaire, Chandra Prakash; Pokhrel, Babu Ram (International Journal of Applied Sciences and Biotechnology, 2019)
Anemia of schedule caste women in Rural area ofeastern Nepal is a prominent problem in developing countries. On the present study is to determine the prevalence of anemia of schedule caste women of Baijnathpur, eastern Nepal. A Cross sectional study was conducted to the schedule caste non -pregnant women of the age group 20 - >70 years during August - November 2015.A total 432 women were participant in the present study. Cyanmethamoglobin used for the determination of anaemia. The prevalence of anaemia was found to be 242(56%) out of N= 432 women. Anaemia was classified as per the world health organization (WHO), mild, moderate and severe. The highest prevalence of anaemia 66.7% was found at the age group of 50-59 years and second highest 59.3% was found at the age group of 20-29 years of the anaemic population. The mean and SD of haemoglobin were 11.49±2.05gm/dl and 10.14±1.57 gm/dl of total and anaemic population respectively Int. J. Appl. Sci. Biotechnol. Vol 7(2): 264-268